2012
DOI: 10.1007/s12013-012-9354-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics and Effect of Human Umbilical Cord Mesenchymal Stem Cells (hUC-MSCs) Grafting with Blood Plasma on Bone Regeneration in Rats

Abstract: We evaluated the biological characteristics/effect of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) grafting with blood plasma on bone regeneration in rat tibia nonunion. SD rats (142) were randomly divided into four groups: fracture group (positive control); nonunion group (negative control); hUC-MSCs grafting with blood plasma group; and hUC-MSCs grafting with saline group. Rats were administered tetracycline (30 mg/kg) and calcein blue (5 mg/kg) 8 days before killing. The animals were kille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…PLT-related parameters, including platelet count, volume, mean volume and distribution width decreased post-operation compared to pre-operation. Similar results on safety have been reported in our previous study, in which we injected hUC-MSCs into rats and found hUC-MSCs located in the rat non-union area that differentiated into osteoblasts, as well as no local or systematic manifestations of toxic reactions and graft vs. host disease during and after transplantation (11,12). Based on the above results, this approach is relatively safe.…”
Section: Discussionsupporting
confidence: 89%
“…PLT-related parameters, including platelet count, volume, mean volume and distribution width decreased post-operation compared to pre-operation. Similar results on safety have been reported in our previous study, in which we injected hUC-MSCs into rats and found hUC-MSCs located in the rat non-union area that differentiated into osteoblasts, as well as no local or systematic manifestations of toxic reactions and graft vs. host disease during and after transplantation (11,12). Based on the above results, this approach is relatively safe.…”
Section: Discussionsupporting
confidence: 89%
“…Guillot PV et al, using a mouse model of OI, have demonstrated that there existed a clinically relevant reduction in incidence rate of bone fracture and huge improvement in the reparative bone tissue with the transplantation of hUC-MSCs [25] . In the stem cell transplantation groups, autologous hUC-MSCs had differentiated into bone cells and large numbers of new multi-center bone growth occurred, highlighting their therapeutic potential for bone repair and healing [14,21,28] .…”
Section: Prospect Of Bone Repair and Healingmentioning
confidence: 99%
“…In additional, hUC-MSCs shared most of the features with MSC from bone marrow, including their morphology and biological characteristics [10] . A great quantity of evidence showed that hUC-MSCs have great potential for self-renewal and multipotential differentiation, which can be differentiated into osteogenic cells, adipogenic cells, neural cells, cartilage cells and others under specific induction of certain factors or stimulation [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs can be isolated from various tissues, including bone marrow, adipose tissue, synovium, periosteum, skeletal muscles, and umbilical cord tissues (8). In previous studies, we demonstrated the immunologic compatibility and osteogenic properties of human umbilical cord-derived mesenchymal stem cells (Hu-MSCs)in tibia non-union in rats (9,10) and patients (11). The primary aim of the present study was to examine in cerebral hemorrhage both with bone marrow mononuclear cells/Hu-MSCs and with conventional surgical approaches, which enhanced regenerative support from transplanted cells to effectively treat acute and chronic disorders of the nervous system.…”
Section: Introductionmentioning
confidence: 99%